Analytical development of impact response of stiffened composite panel with optimum structural behaviour - Cruz Reyes, José Juan; Ghasemnejad, Hessam (MDPI, 2026)
This paper presents an analytical framework for the preliminary design of stringer-stiffened composite panels subjected to low-velocity impact. The formulation combines First-Order Shear Deformation Theory with a two-degree-of-freedom spring–mass model, while the super-stringer is represented as a Euler–Bernoulli beam whose bending contribution is transferred to the skin mid-surface through the parallel axis theorem. This provides a computationally efficient tool for rapid parametric assessment of stiffened configurations at the early design stage. To support laminate selection, a Specific Impact Energy Index (SIEI) is introduced to rank configurations according to their elastic energy storage efficiency relative to the product of skin and stringer thicknesses. The tool is validated against both published experimental results and a finite element dynamic explicit model, demonstrating a good approximation of the impact response. It is then applied to identify the optimum laminate configuration for a super-stringer case study within the design space considered.
This article belongs to the Special Issue Characterization and Modeling of Composites, 4th Edition
Keywords: 40 Engineering; 4001 Aerospace Engineering; 7 Affordable and Clean Energy; 4016 Materials engineering; impact; composites; spring-mass; stringer-stiffened panel